Sexual knowledge, sexual science : the history of attitudes to sexuality - Porter, Roy; Teich, Mikulas (Cambridge : Press Syndicate of the University of Cambridge, 1994)
Fonds Suzan Daniel (FSD)
Engels
Monografie